The evolution of hepatitis B and nutritional support: Case report - Alencar , Shellda Azevedo; Silva , Isabele Paula da; Nogueira , Danila Torres de Araujo Frade (Seven Editora, 2023)
Hepatitis B is an infectious disease caused by contact with a source that is positive for both the HBV surface antigen and the “e” antigen of the virus. Hepatitis B is a silent disease and therefore the diagnosis is usually late, favoring the chronicity of diseases that affect the liver. The objective of this article is to present a case study of hepatitis B and its complications, and the nutritional interventions performed during hospitalization. This is an experience report of monitoring the treatment of a patient affected by hepatitis B and other diseases in the mandatory hospital experience in the discipline of diet therapy II, of the bachelor's degree in nutrition, held at the Hospitalar Foundation of Acre. The progression of liver disease has an impact on nutritional status because it is related to a decrease in energy and protein intake, affected by food restrictions and low-palatable diets, which directly interfere with food consumption. After the patient's follow-up period, it was not possible to observe evolution in his health status, it was possible to identify the progression of the disease through imaging, biochemical and physical exams. DOI:https://doi.org/10.56238/emerrelcovid19-054